Food plants in Brazil: origin, economic value of pollination and pollinator shortage risk - Oliveira, Willams; Colares, Lucas F.; Porto, Rafaella G.; Viana, Blandina F.; Tabarelli, Marcelo; Lopes, Ariadna V. (The Science of the total environment, 2024)
Pollination is a key ecosystem service of critical importance for food production. However, globally, several regions are already experiencing pollinator shortage as pollinators are declining. Here, we investigate the origin, pollinator dependence and economic value of 199 food crops cultivated in Brazil to understand to which extent (1) Brazilian agriculture is vulnerable to pollinator shortage, and (2) Brazilian society has already achieved a comprehensive perspective about crop dependence. We used Brazil as a case study as it is a megadiverse tropical country and the 3rd largest world crop producer and exporter, with most of the crops depending on pollinators. Our findings revealed that over half (53.7%) of the food crops in Brazil are native, with the North region of Brazil housing the higher diversity of native crops, in contrast with the South and Southeast regions. Additionally, considering the reproductive systems, among native food crops, 65.6% exhibit self-incompatibility or dioecy (i.e., requiring obligatory cross-pollination), whereas 30.6% of exotic food crops display this trait. Overall, Brazilian municipalities produce more exotic crops than native ones, with almost 4/5 of the total agricultural area of the country dedicated to the cultivation of exotic crops, which are generally self-compatible commodities that rely low to modestly on pollinators. Regarding the biomes, we observe that this pattern is followed by most of them, but for the Caatinga dry forest, where native crops dependent on pollinators predominate. However, when soybean is removed from the analysis, the areas devoted to exotic crops always decreased, even being equal to native crops in the Atlantic forest. Our results also indicate that considering the pollinator shortage, some Brazilian biomes may be at risk of losing >20% of their yields, mainly in the Caatinga dry forest and the Atlantic forest. Therefore, in this paper, we are discussing that the expansion of monocultures in Brazil's agricultural lands may have several impacts on the provision of pollination services, food production and, then, on food security not only for the Brazilian population, as Brazil is the 3rd largest world agricultural producer and exporter. [Display omitted] •Apis mellifera interacts extensively with native and exotic crops, while vertebrates exclusively pollinate native crops•71.4% of native food crops have essential pollinator dependence, contrasting the 30.2% of exotic•81.5% of the total agricultural area in Brazil is cultivated with exotic food crops, of which 46% is soybean•For native crops, pollinator shortage risk is mainly concentrated in the Northeast and Southeast Brazilian regions•Considering the Brazilian biomes, the Atlantic forest is at higher risk of pollinator shortage